2008
DOI: 10.1007/s11103-008-9430-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel wall-associated receptor-like protein kinase gene, OsWAK1, plays important roles in rice blast disease resistance

Abstract: Wall-associated protein kinases (WAKs) are a new group of receptor-like kinases (RLK) recently identified in Arabidopsis. A cDNA encoding a novel WAK was isolated from rice and was named OsWAK1 (Oryza sativa WAK). The deduced amino acid sequence of OsWAK1 showed 27.6% identity to WAK2 from Arabidopsis. OsWAK1 not only has the ability of autophosphorylation but also can phosphorylate OsRFP1, a putative transcription regulator recently identified in rice. OsRFP1 strongly interacts with the kinase domain of OsWAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 42 publications
0
112
2
Order By: Relevance
“…Such an expression pattern was also observed for genes encoding proteins containing protein kinase (Fig. 2b), leucine-rich, NB-ARC and EF-hand domains, which might function in signal transduction for defence systems (Kandoth et al, 2007;Lee & Rudd, 2002;Li et al, 2009;Syam Prakash & Jayabaskaran, 2006;Tameling & Baulcombe, 2007). These observations indicate that host defence systems associated with genes for transcription factors such as WRKY (OsWRKY45; Shimono et al, 2007) and NAC (ONAC28; Fang et al, 2008), and signal transduction-related genes such as those for protein kinase (CDPK) and receptor protein (NBS-LRR), were not activated at the early phase of RSV infection, but some steps of these systems were induced at the late phase, when the infected plants showed obvious symptoms.…”
Section: Modification Of Host Defence Systems By Rsv Infectionmentioning
confidence: 63%
“…Such an expression pattern was also observed for genes encoding proteins containing protein kinase (Fig. 2b), leucine-rich, NB-ARC and EF-hand domains, which might function in signal transduction for defence systems (Kandoth et al, 2007;Lee & Rudd, 2002;Li et al, 2009;Syam Prakash & Jayabaskaran, 2006;Tameling & Baulcombe, 2007). These observations indicate that host defence systems associated with genes for transcription factors such as WRKY (OsWRKY45; Shimono et al, 2007) and NAC (ONAC28; Fang et al, 2008), and signal transduction-related genes such as those for protein kinase (CDPK) and receptor protein (NBS-LRR), were not activated at the early phase of RSV infection, but some steps of these systems were induced at the late phase, when the infected plants showed obvious symptoms.…”
Section: Modification Of Host Defence Systems By Rsv Infectionmentioning
confidence: 63%
“…Wall-associated kinases have been found to play a role in disease resistance (30,31), phosphorus-starvation tolerance (32), and developmental processes such as root growth (33) and gametophyte development (34). A recent study reported that the maize quantitative head smut resistance gene qHSR1 also encodes a wall-associated kinase.…”
Section: Resultsmentioning
confidence: 99%
“…Through an extracellular domain, wall-associated kinases physically link the plasma membrane to the cell wall matrix. They also have the potential to directly signal cellular events through their cytoplasmic kinase domain, which is one of the most likely candidates participating in cell wall-cytoplasm signaling in plant defense reactions [26]. All of these results suggest that the higher activity of defensive proteins and membrane fluidity under control conditions might be involved in CT in K354.…”
Section: Resultsmentioning
confidence: 99%